2003
DOI: 10.1152/ajpendo.00021.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting NOS blocks microvascular recruitment and blunts muscle glucose uptake in response to insulin

Abstract: . Inhibiting NOS blocks microvascular recruitment and blunts muscle glucose uptake in response to insulin. Am J Physiol Endocrinol Metab 285: E123-E129, 2003; 10.1152/ajpendo.00021.2003.-We examined the effects of inhibiting nitric oxide synthase with N -nitro-L-arginine-methyl ester (L-NAME) on total hindlimb blood flow, muscle microvascular recruitment, and hindlimb glucose uptake during euglycemic hyperinsulinemia in vivo in the rat. We used two independent methods to measure microvascular perfusion. In one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
313
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 272 publications
(328 citation statements)
references
References 34 publications
(60 reference statements)
13
313
1
1
Order By: Relevance
“…Similarly, other studies have shown that endothelium-dependent vasodilation was impaired in thoracic aorta rings from rats infused with glucosamine and that this was a result of the inhibition of NOS by glucosamine [19]. Since both the insulin-mediated increases in total flow [15,36] and capillary recruitment [16] have been suggested to be NOSdependent, this could be the mechanism for the glucosamine-mediated inhibition of capillary recruitment and total flow. The effects of glucosamine on gene expression in endothelial cells [37] should also be considered, if longer-term exposure occurs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, other studies have shown that endothelium-dependent vasodilation was impaired in thoracic aorta rings from rats infused with glucosamine and that this was a result of the inhibition of NOS by glucosamine [19]. Since both the insulin-mediated increases in total flow [15,36] and capillary recruitment [16] have been suggested to be NOSdependent, this could be the mechanism for the glucosamine-mediated inhibition of capillary recruitment and total flow. The effects of glucosamine on gene expression in endothelial cells [37] should also be considered, if longer-term exposure occurs.…”
Section: Discussionmentioning
confidence: 78%
“…When infused locally [15], inhibitors of nitric oxide synthase (NOS) block insulin-mediated increases in blood flow, and also block insulin-mediated capillary recruitment when infused systemically [16]. For capillary recruitment, the higher sensitivity to insulin [17] and the fact that time course studies show capillary recruitment to be the earliest change caused by insulin in vivo [18] suggest that endothelial cells, in particular endothelial nitric oxide synthase (eNOS), are the source of nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 99%
“…There are two major effectors of muscle glucose uptake, insulin and exercise, and both have been claimed to involve some dependency on NO [1][2][3]26]. In rats, insulin-mediated increase in limb blood flow is blocked by systemically administered NO synthase inhibitors [27,28], as is insulin-mediated capillary recruitment [27,28] and glucose uptake [27,28], although the latter is controversial in humans [24,29,30]. However, since a centrally injected NO synthase inhibitor can mimic the insulin resistance and hypertension seen with systemic NO synthase inhibitors [31], a local mechanism involving endothelial insulin receptors, endothelial NO synthase and NO-dependent vasodilatation is far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased blood flow to skeletal muscle resulting in increased delivery of glucose and insulin to metabolic targets of insulin action (2). These vasodilator actions of insulin contribute significantly to insulin-mediated glucose uptake (3)(4)(5)(6). Synergistic relationships between insulin sensitivity and endothelial function are reinforced because insulin signaling pathways in skeletal muscle, adipose tissue, and liver promoting metabolic actions of insulin are shared in common with insulin signaling pathways in vascular endothelium promoting vasodilator actions of insulin (1).…”
mentioning
confidence: 99%